Wireless water usage monitoring system for home / small premises - W.L. Chee Wei; A.S. Ab Ghafar; N.N. Hairul Rozi; F. A. Saparudin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The fourth Industrial Revolution has led to tremendous change in industrial automation. Measurement system can be seen as an important tool implemented in various fields because it enables us to access essential data from the environment or desired location. One of the essential measurement systems in industry, company or home is water usage monitoring. Water usage monitoring is the regular collection of information on the total amount of water drawn from sources during a given period. It enables a company or industry to understand water usage patterns and identify potential inefficiencies. For instance, a hotel premise who wants to monitor its water usage per room basis. Monitoring is also essential to set reduction targets of water used. The paper presents the development of wireless water usage monitoring system. This system consists of two nodes which are sensor node and sink node. The sensor node collects the water usage data and send them to the sink node. An ultrasonic sensor, Light-Emitting Diode (LED) and buzzer are attached to the sensor node as alert system for the user in case of water wastage occurrence. The sink node receives data from the sensor node wirelessly and mark this data time stamp by referring to a Real Time Clock (RTC) and store it in the database. The database is attached to sink node with Secure Digital (SD) card module. Furthermore, a Graphical User Interface (GUI) is used to display the water usage data in graphical form for easier user interpretation. The proposed wireless water usage monitoring system is suitable for home and small premises usage.